Multi-view geometry based visual perception and control of robotic systems - Chen, Jian; Zhang, Kaixiang; Jia, Bingxi; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This book describes visual perception and control methods for robotic systems that need to interact with the environment. Multiple view geometry is utilized to extract low-dimensional geometric information from abundant and high-dimensional image information, making it convenient to develop general solutions for robot perception and control tasks. In this book, multiple view geometry is used for geometric modeling and scaled pose estimation. Then Lyapunov methods are applied to design stabilizing control laws in the presence of model uncertainties and multiple constraints.
part PART I: FOUNDATIONS -- chapter 1 Robotics -- chapter 2 Multiple-View Geometry -- chapter 3 Vision-Based Robotic Systems -- part PART II: VISUAL PERCEPTION OF ROBOTICS -- chapter 4 Introduction to Visual Perception -- chapter 5 Road Scene 3D Reconstruction -- chapter 6 Recursive Road Detection with Shadows -- chapter 7 Range Identification of Moving Objects -- chapter 8 Motion Estimation of Moving Objects -- part PART III: VISUAL CONTROL OF ROBOTICS -- chapter 9 Introduction to Visual Control -- chapter 10 Visual Tracking Control of General Robotic Systems -- chapter 11 Robust Moving Object Tracking Control -- chapter 12 Visual Control with Field-of-View Constraints -- chapter 13 Visual Control of Mobile Robots -- chapter 14 Trifocal Tensor Based Visual Control of Mobile Robots -- chapter 15 Unified Visual Control of Mobile Robots with Euclidean Reconstruction.
Keywords: ElectricalEngineeringnetBASE; Intelligent Systems; Linear control systems; Neural computers; Robotics; Systems & Controls; CRC/IHC Default Subject Code; TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Robotics; Compter vision; Robots -- Control systems